Pharmaceuticals: Who's afraid of '1992'? - Gernot Klepper (Centre for Economic Policy Research (CEPR); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
This paper develops a framework within which the impact of the proposed initiatives of the European Commission for creating an internal market for pharmaceuticals can be analysed. In a model of third-degree price discrimination, arbitrage between two markets and price controls through governments in one market are introduced. The effects of easier arbitrage opportunities, i.e. lower arbitrage costs, on the prices in the two markets are analysed. Also, the impact of a reduction in price controls in the low-priced markets as well as their combined effects are characterized. The welfare effects of the Internal Market in pharmaceuticals are ambiguous, since a movement from segmented and price-controlled markets towards integrated markets does not lead to a first- or second-best solution.
Keywords: O43; O60; F13; F15; 330